Pengaruh Dana Pihak Ketiga, Return on Aset dan Non-Performing Financing Terhadap Financing to Deposit Ratio - Syiffa Nur Pratama; Hasbi Assidiki Mauluddi; Destian Arshad Darulmalshah Tamara (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
This study aims to determine the influence of Third Party Funds (DPK), Return On Asset (ROA) and Non Performing Financing (NPF) on the decrease in Financing to Deposit Ratio (FDR) at PT Bank Muamalat Indonesia. In this study, the data used in the form of secondary data in the form of Annual Financial Report of PT Bank Muamalat Indonesia for the period 2013-2020 published by Bank Muamalat Indonesia. Technical analysis used is multiple regression using SPSS software. The results obtained from this study indicate that simultaneously Third Party Funds (DPK), Return On Assets (ROA and Non Performing Financing (NPF) have a significant effect on the Financing to Deposit Ratio (FDR) at PT Bank Muamalat Indonesia. (DPK) and Return On Assets (ROA) have a significant effect on the Financing to Deposit Ratio (FDR) at PT Bank Muamalat Indonesia, while Non Performing Financing (NPF) has no significant effect on the Financing to Deposit Ratio (FDR) at PT Bank Muamalat Indonesia. This performance appraisal is expected to be used as a proposal for banks to maintain the composition of the level of liquidity that must be maintained. This performance assessment is expected to be used as a proposal for banks to maintain the composition of liquidity levels that must be maintained.